Analisis Pengaruh Komposisi Kimia dan Suhu Perlakuan Panas Terhadap Sifat Mekanik Baja Tahan Karat untuk Aplikasi Konstruksi - Ade usra Berli; Desmarita Leni; Helga Yermadona (SURYA TEKNIKA, 2023)
A deep understanding of the mechanical properties of stainless steel is crucial for designing constructions that meet the requirements. However, to comprehensively understand the mechanical properties of stainless steel, sufficient testing is needed to gather data regarding its characteristics. In this research, an analysis was conducted on the Effect of Chemical Composition and Heat Treatment on the Mechanical Properties of Stainless Steel, using data from the Material Algorithm Project (MAP), which is a material database. The data was analyzed using descriptive statistics and Pearson correlation to observe the relationships between these variables. The research results indicate that chemical elements such as Cu and Ni have a positive correlation with elongation, indicating that higher concentrations of these elements lead to higher elongation of stainless steel. Furthermore, it was also found that temperature has a strong negative correlation with yield strength (YS) and ultimate tensile strength (UTS), with correlation values of -0.71 and -0.86, respectively. Further analysis revealed that water quenching resulted in better ultimate tensile strength compared to air quenching. This research demonstrates that experimental material testing datasets not only validate experiments but can also actively be used in the analysis and design of more effective materials.